A fundamental re-conceputalization of intelligence: cognitive activity and the pursuit of advantage. Issue 2 (23rd February 2022) - Cox, James
ABSTRACT: This paper argues that human intelligence is the fundamental form of intelligence, and that cognitive activity is the premier component of the intelligence process. As practiced in the national security paradigm, intelligence is essentially humankind's attempt to replicate human intelligence in purposeful social groups. Further analysis suggests that the pursuit of advantage is the central focus of true intelligence. Accordingly, a new universal definition defines intelligence as the capacity for reasoned foresight that enables advantageous action. The traditional cycle is subsequently re-conceptualized as a cognition-centric Intelligence Enterprise Model (IEM) that provides a more useful framework for future intelligence enterprise development.